Analisis Beban Kerja Menggunakan Metode Full Time Equivalent Pada Departemen Produksi PT XYZ - Ayu Wandini Aprilia; Maulidyah Amalina Rizqi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Product A at PT XYZ is one of the leading products that is in great demand by customers, which is characterized by an increase in sales in recent years. Therefore, to be able to ensure that customer demand can be met properly, the company must pay attention to human resources related to the production process. For this reason, the measurement of workload in the production department needs to be carried out with the aim of updating the actual data related to the workload borne by workers, so that the optimal number of workers can be known, besides that it can be used as a basis for determining policies when carrying out the recruitment process in the future. This research was conducted using the Full Time Equivalent (FTE) method, and the results obtained are that the production admin worker has a workload of 1.03 (labor required 1) and a fit workload, shift 1 production operators have a workload of 1 per three people (labor required 3) workload in a fit condition, shift 2 production operators have a workload of 0.82 per 2 operators (labor required 2) but the workload is still underload and finishing workers of 1.08 (labor required 1) workload in a fit condition.